Biogeochemical and Microbial Variation across 5500 km of Antarctic Surface Sediment Implicates Organic Matter as a Driver of Benthic Community Structure - Learman, Deric R.; Henson, Michael W.; Thrash, J. Cameron; Temperton, Ben; Brannock, Pamela M.; Santos, Scott R.; Mahon, Andrew R.; Halanych, Kenneth M. (Frontiers in Microbiology, 2016)
Western Antarctica, one of the fastest warming locations on Earth, is a unique environment that is underexplored with regards to biodiversity. Although pelagic microbial communities in the Southern Ocean and coastal Antarctic waters have been well studied, there are fewer investigations of benthic communities and most have a focused geographic range. We sampled surface sediment from 24 sites across a 5,500 km region of Western Antarctica (covering the Ross Sea to the Weddell Sea) to examine relationships between microbial communities and sediment geochemistry. Sequencing of the 16S and 18S rRNA genes showed microbial communities in sediments from the Antarctic Peninsula (AP) and Western Antarctica (WA), including the Ross, Amundsen, and Bellingshausen Seas, could be distinguished by correlations with organic matter concentrations and stable isotope fractionation (total organic carbon; TOC, nitrogen, and δ13C). Overall, samples from the AP were higher in nutrient content (TOC, nitrogen, and NH4+) and communities in these samples had higher relative abundances of operational taxonomic units (OTUs) classified as the diatom, Chaetoceros, a marine cercozoan and four OTUs classified as Cytophaga or Flavobacteria. As these OTUs were strongly correlated with TOC, the data suggests the diatoms could be a source of organic matter and the Bacteroidetes and cercozoan are grazers that consume the organic matter. Additionally, samples from WA have lower nutrients and were dominated by Thaumarchaeota, which could be related to their known ability to thrive as lithotrophs. This study documents the largest analysis of benthic microbial communities to date in the Southern Ocean, representing almost half the continental shoreline of Antarctica, and documents trophic interactions and coupling of pelagic and benthic communities. Our results indicate potential modifications in carbon sequestration processes related to change in community composition, identifying a prospective mechanism that links climate change to carbon availability.